Serbs and Slovaks, Matica Srpska and Matica Slovenská: Two centuries of trials and experiences - Negrišorac, Ivan (Napredak, 2026)
Two Slavic peoples, Serbs and Slovaks, Slovaks and Serbs, serve as a good example of nations with close common origins, who, throughout their existence, have not easily forgotten this shared heritage. This common origin enables them even today, after many centuries, to understand each other well and to have meaningful dialogue. A developed consciousness of kinship, rooted as much in the facts of common origin as in the realities of mutual understanding, allows these two peoples not only to examine the obscure and unclear events of the past but also to project related visions of the future. Only by combining these two profound and distant temporal dimensions, expressed in the intersection we call the ever-relevant present, should one seek to construct one’s collective, national destiny and concrete historical reality. Such construction, in turn, should not rely solely on adapting to general, global, externally imposed circumstances but also on actively shaping a sense of meaning that reveals itself to a Slavic people as a credible value of human life, the kind of life that is possible in this time and in this world.
Keywords: Serbs; Slovaks; Matica Srpska; Matica slovenská; Georgije Magarašević; Pavel Jozef Šafárik; Ján Kollár; Svetozar Miletić